Características clínicas, estado nutricional e alimentação de lactentes em dieta de exclusão das proteínas do leite de vaca em comparação com lactentes sem restrições alimentares - Augusto, Erika Ozela [UNIFESP] (2019)
Objective: To study the clinical characteristics, anthropometry and nourishment of infants in a cows' milk exclusion diet. Methods: A cross-sectional study comparing two groups: 1. in a cows' milk exclusion diet (n = 60) and 2. without dietary restrictions (n=60). During the interview, clinical, nutritional and economic information were collected. Weight and length were measured. Results: 41.7% of infants in the study group had restriction to other foods besides cow's milk. Infants in the exclusion diet, compared to the control group, had lower values (p <0.05) for length-age z score (-0.4 ± 1.6 vs + 0.2 ± 1.3) lower daily energy intake (1253.7 vs 1364.5 calories), lipids (41.9 vs 55.5 g); phosphorus (476.7 mg vs. 618.5 mg); sodium (794.7 vs 1118.5 mg) and potassium (1099.3 vs. 1525.6 mg). Macronutrients intake from all infants of both groups reached the recommendations for sex and age. Between 12 and 24 months, the proportions of infants in the exclusion diet who never consumed beef (14.7% vs. 0.0%), fish (23.5% vs 3.0%), cereals (41.2% vs 6.01%) and egg (14.7% vs 0.0%) were higher in relation to the control group (p <0.05). Conclusions: The group in the exclusion diet presented lower linear growth, according to the z scores of length-age. The diet of all infants with lactose intolerance reached the macronutrient recommendations. It was also observed a delay in the introduction of several foods in the diet of patients on exclusion diet.